Changes in the organic carbon resources in successive forest development stageson dunes in the Toruń Basin - Deptuła, Miłosz; Kruczyńska, Anna (Ecological Questions, 2015)
One way to prevent the growing carbon dioxide amount in the atmosphere consists in afforestation of forest wastelands such as: heaths, peat bogs, swamps. Replacing such ecological systems by planting them with trees allows to increase the afforested area and, at the same time, to increase the accumulation of organic carbon in the plant biomass. The growing contribution of forest stands may lead to natural restoration, mostly by self-seeding. This study determined changes in the organic carbon resources at the following stages of the natural succession occurring on heaths. The changes were compared with values obtained for the pine cultivation developed from artificial afforestation of the inland dune. The study was conducted on the heathland near the southern boundary of Toruń. Four plots were established in the gradient of the increasing density of pine. The second object of the study was an artificial pine cultivation established on the suburban inland dune (Zadroże Dune). The heather was preserved in abundant quantities in places where wilding pine trees occurred in small numbers (plot I), whereas in places with older self-sown plants (plots III and IV), the heath covered only a small part of the study area, beneath the canopy gaps allowing greater sunlight penetration. The artificial forest cultivation established on a dry habitat with trees three times older compared to self-sown pines on the heathland accumulates similar amounts of carbon in the biomass. The performed analysis showed that there are no significant differences in the carbon resources accumulated in the artificial and well-developed forest ecosystem (ca. 108.30 t Corg./ha) compared to carbon resources in the naturally developing area (plot IV; 94.61 t Corg./ha).